A review of Diphuia (Diptera: Ephydridae) with description of two new species from southern Brazil - Wayne N. Mathis; Luciane Marinoni (Zoologia (Curitiba), 2010)
The species of Diphuia Cresson, 1944 are reviewed with an emphasis on the fauna from southern Brazil, where two new species have been discovered and herein are described: Diphuia antonina sp. nov. and Diphuia grandis sp. nov. All known species are placed into two species groups (the anomala and nitida groups), which are characterized, and a key to these species is included. To facilitate identification of species of this uncommon genus, we have included diagnoses of the genus and tribe Hecamedini and have also provided an annotated key to New World genera in the tribe and to the known species of Diphuia. We have also provided illustrations of structures of the male terminalia of all included species.The species from southern Brazil, including the new ones, are illustrated.